United Arab Emirates : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in the United Arab Emirates during 1995-98. Real GDP growth accelerated from about 5 percent in 1994 to 8.1 percent in 1995 and to 10.1 percent in 1996. However, 1997 saw a marked slowdown in real GDP growth, to an estimated 2.1 percent, reflecting mainly a decline in oil sector GDP. Over the period 1993-96, there was strong growth in non-oil GDP averaging 9 1\2 percent per year, boosted by an exceptionally good performance in 1994 (12 percent).